2018
DOI: 10.3390/rs10111825
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Imputation Approaches for Estimating Forest Biomass Using Landsat Time-Series and Inventory Data

Abstract: The prediction of forest biomass at the landscape scale can be achieved by integrating data from field plots with satellite imagery, in particular data from the Landsat archive, using k-nearest neighbour (kNN) imputation models. While studies have demonstrated different kNN imputation approaches for estimating forest biomass from remote sensing data and forest inventory plots, there is no general agreement on which approach is most appropriate for biomass estimation across large areas. In this study, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In terms of tasseled cap, its components have been widely used in biomass estimation [14,21,39]. Brightness, greenness, and wetness were successively selected as important predictor variables, similar to other Landsat-related biomass estimation research [40]. However, it has been stated that Landsat 8 has a refined near-infrared spectral band for more accurate spectral acquisition when compared to the Landsat former series [11], but the advantage in the near-infrared band of OLI Band 5 over TM Band 4 remains to be further investigated.…”
Section: Comparison Of Variable Importancementioning
confidence: 99%
“…In terms of tasseled cap, its components have been widely used in biomass estimation [14,21,39]. Brightness, greenness, and wetness were successively selected as important predictor variables, similar to other Landsat-related biomass estimation research [40]. However, it has been stated that Landsat 8 has a refined near-infrared spectral band for more accurate spectral acquisition when compared to the Landsat former series [11], but the advantage in the near-infrared band of OLI Band 5 over TM Band 4 remains to be further investigated.…”
Section: Comparison Of Variable Importancementioning
confidence: 99%
“…Our MODIS model relative RMSE (48.47%) was consistent with other studies such as that of Reference [79], which revealed an RMSE% of 69% for aboveground tree biomass estimated by NFI ground plots and 250 m MODIS data. However, other studies, which a large amount of Landsat data, provided lower RMSE% at regional scale [80].…”
Section: Forest Agb Estimate From Local To National Scalementioning
confidence: 79%
“…For example, Matasci, Hermosilla [51] and Nguyen, Jones [52] used this method for large area predictions of AGB dynamics through 30-year periods in Canada and southeast Australia, respectively. Studies comparing different kNN distance techniques used for imputing forest attributes often indicated the outperformance of RF [8,56,96].…”
Section: Statistical Modelling Techniquementioning
confidence: 99%
“…The accuracy of AGB predictions can be enhanced as it is imputed based on another variable (or group of variables) that has higher correlation with predictors. Nguyen, Jones [56] found that AGB can be better predicted using an indirect imputation approach combining a group of basal area and stem density variables with LTS. In addition, other forest attributes, along with AGB, can be mapped directly without new model developments.…”
Section: Statistical Modelling Techniquementioning
confidence: 99%